La syntaxe et la sémantique des démonstratifs prédicatifs en français, en chinois mandarin et en vietnamien : perspective typologique - Fanguang Kong; Huy Linh Dao (Corela, 2024)
This article proposes a comparative and typological study of predicative demonstratives in French, Mandarin Chinese and Vietnamese. Six class of predicative demonstratives have been described one after another: presentive demonstratives, identification demonstratives, localizing demonstratives, copular demonstratives, manner demonstratives and implicit demonstratives. This research makes it possible to underline the syntactic and semantic characteristics of predicative demonstratives in the three languages, in the sense that they often function as non-verbal predicates without subjects and playing a role of reference or discourse-pragmatics. The predicative demonstratives in Mandarin Chinese and Vietnamese have another particularity because a demonstrative morpheme can be used in several morphosyntactic categories.